Influence of oral health care systems on future career environment of dental students in Europe - Wolf, Thomas Gerhard; Otterbach, Ernst-Jürgen; Zeyer, Oliver; Wagner, Ralf Friedrich; Crni´c, Tin; İlhan, Duygu; Campus, Guglielmo (MDPI AG, 2021)
Oral healthcare is organized subsidiarily and independently by nation states in Europe and also within the EU and consequently, major differences between the nation states and the various oral healthcare systems in Europe are present. The socialization in the respective catchment area can have an impact on the job choice and the perception of employment opportunities of different professional groups. Therefore, the purpose of this survey was to elucidate the influence of different oral healthcare systems on students living or studying in the respective catchment area. A questionnaire (in English, French, German, Italian, and Spanish) with 18 different components was administered. Data on gender, age, country of origin, university, semester, nationality, expected time of graduation, and forecast for future professional practices were gathered. In addition, 3851 students participated (2863 f/988 m). The sample distribution was uneven with predominantly Bismarckian and Southern European System participants. The National oral health care system was statistically significantly linked (p < 0.01) to the ownership period of a dental practice. Students in Bismarckian and Nordic systems tended to find their own practice earlier than in the Beverdigian system or Southern European and Transitional—East European systems. An association between the oral health care system and vocational training was inhomogeneous, but also significantly different (p <0.01). The majority (47.51%, n = 1555) would like to work in their own practice, 18.95% (n = 621) want to establish a practice with two or more owners. It was striking that no student would like to work in the investor practice/practice chain of both Nordic, Beveridgian and Transitional—East European countries systems (p < 0.01). The oral health care system in which a dental student grows up/resides/studies influences the career choice/perception of future professional practice.
Keywords: Dental Practice; Dental Students; Europe; Expectations; Future Career; Oral Health Care System